2020
DOI: 10.3390/vetsci7010012
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antibacterial Activity of Biological-Derived Silver Nanoparticles: Preliminary Data

Abstract: Silver nanoparticles (AgNPs) are promising alternatives to antibiotics. The aims of this study were to produce AgNPs using two biological methods and determine their antibacterial activity against Pseudomonas aeruginosa and Staphylococcus pseudintermedius. AgNPs were biosynthesized from an infusion of Curcuma longa (turmeric) and the culture supernatant of E. coli. Characterization was achieved by ultraviolet-visible spectroscopy and by Transmission Electron Microscopy (TEM). The antibacterial properties of NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…The abilities against S. pseudintermedius were not identified. In this study, we verified the antibiofilm abilities of AgNPs at various concentration compared with a study reported previously (Meroni et al., 2020).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The abilities against S. pseudintermedius were not identified. In this study, we verified the antibiofilm abilities of AgNPs at various concentration compared with a study reported previously (Meroni et al., 2020).…”
Section: Discussionsupporting
confidence: 90%
“…Some products intended for dogs that contain AgNPs are also available, but little is known about their microbial activity against veterinary relevant pathogens (Bae et al., 2017). A single preliminary study of the antibiofilm activity of AgNPs on S. pseudintermedius isolated from dogs currently exists (Meroni et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The results show that the antimicrobial efficiency was followed by S1, S2, S3, S4 and S5, which can be divided into two groups: S1–S2 (MIC/MBC ≤ 32 µg/mL) and S3–S5 (MIC/MBC ≤ 100 µg/mL). Our results are the same as a previous report by Gabriele Meroni et al, 2020 and Katarzyna A et al, 2017 [ 39 , 40 ]; AgNPs have strong antibacterial abilities to S. pseudintermedius . In a comparison of all AgNPs, S1 and S2 were very close in MIC and MBC.…”
Section: Discussionsupporting
confidence: 93%
“…Combinations containing conventional antibacterials are already practiced in clinical settings to combat resistant Gram-positive and Gram-negative strains (Eades et al, 2017;Jacobs et al, 2017;Doi, 2019). BioAgNP showed antimicrobial synergistic or additive effect when combined with several essential oils, their main constituents, and other natural compounds (Cardozo et al, 2013;Biasi-Garbin et al, 2015;Otaguiri et al, 2016;Scandorieiro et al, 2016;Dehkordi et al, 2019), and some conventional antimicrobials and other materials or drugs (Kora and Rastogi, 2013;Longhi et al, 2016;Andrade et al, 2017;Bankier et al, 2019;Bocate et al, 2019;Figueiredo et al, 2019;Vazquez-Muñoz et al, 2019;Meroni et al, 2020) such as phenazine-1-carboxamide, eugenol, oregano oil, copaiba oil, carbon dots, tungsten carbide nanoparticles, cupper nanoparticles, simvastatin, fluconazole, carbenicillin, streptomycin, ampicillin, tetracycline, kanamycin, and chloramphenicol. Other studies have also reported an antimicrobial synergistic or additive effect of oregano derivatives in combination with others natural compounds (Ayari et al, 2020;Cho et al, 2020) and several conventional antimicrobials (Hamoud et al, 2014;Langeveld et al, 2014;Yap et al, 2014;Magi et al, 2015;Xiao et al, 2020) such as cinnamon essential oil, thyme-derived Thy, cinnamon bark essential oil, erythromycin, fluoroquinolones, doxycycline, lincomycin, vancomycin, amoxicillin, gentamicin, levofloxacin, ciprofloxacin, rifampin, and polymyxin.…”
Section: Discussionmentioning
confidence: 99%